The eyes and voices of International Students in Australian University - Poedjiastutie, Dwi (Lambert Academic Publishing, 2013)
This present study was intended to investigate the international students' perceptions of the roles of tutors in Australian universities. Cultural issues are important in defining the roles of tutors and international students studying in Australia may have different perceptions of the appropriate roles of tutors at tertiary level. Teaching is a complex cultural activity. Therefore, tutors and students need to understand each other within the socio-cultural contexts that have shaped their attitudes. It is suggested to tutors who are working with culturally mixed population that they not act exclusively as facilitator but occasionally shift roles and functions in different ways such as information provider, counselor, planner, and evaluator. Moreover, tutors should make their expectations more explicit and encourage the overseas students participation in classroom discussion gently.